The diagnosis of intramural esophageal squamous cell carcinoma without mucosal invasion using endoscopic ultrasound-guided fine needle aspiration biopsy: A case report. Issue 27 (2nd July 2020) - Pan, Hanghai; Zhou, XinXin; Zhao, Fei; Lou, Guochun
Abstract: Rationale: Intramural esophageal squamous cell carcinoma (ESCC) without mucosal invasion is extremely rare. Endoscopic mucosal biopsy results are often negative, making diagnosis difficult. In these cases, endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) biopsy is a useful diagnostic method. Patient concerns: A 78-year-old female was admitted to hospital due to dysphagia, and gastroscopy showed a concentric narrowing of the esophageal lumen with a smooth and undamaged esophageal mucosa. Diagnoses: Endoscopic ultrasound (EUS) revealed that the esophageal mucosa was thickened with a low echo, and the layers of the esophageal wall could not be clearly distinguished. Cytologic and pathologic diagnoses were obtained through EUS-FNA, which suggested ESCC. Interventions: According to the pathologic diagnosis obtained by EUS-FNA, surgery or radiotherapy were recommended for this patient. Eventually, this patient elected to seek treatment at another medical institution. Outcomes: This type of disease cannot be diagnosed according to gastroscopic biopsy alone, and the diagnosis was eventually confirmed through EUS-FNA. Lessons: When an imaging examination suggests a possible malignant lesion of the oesophagus, EUS-FNA may be considered if the surface mucosa contains no endoscopic damage. EUS-FNA has high diagnostic value with high sensitivity, minimal invasiveness, and high safety.